Atypical haemolytic-uraemic syndrome: reflecting over the old and new - Farinha,Ana (2012)
Atypical haemolytic uraemic syndrome is a rare disease characterised by microangiopathic haemolytic anaemia, thrombocytopaenia and predominant renal impairment in the absence of Shiga toxin-producing bacteria. For long time it has been difficult to distinguish it from other thrombotic microangiopathies, but in the last decade advances have been made in understanding the pathogenesis of atypical haemolytic uraemic syndrome as a disorder of alternative pathway of the complement system. Knowledge of mutations and polymorphisms in the genes encoding the complement regulatory proteins revealed clinical importance in the management of the patients, altering not only the transplantation perspective but also leading to the search for new drugs, something that will potentially change the poor prognosis of these patients. This article reviews the differential diagnosis of this thrombotic microangiopathy to reflect on current treatment options and discuss new therapies